Jane Austen and marriage - Jones, Hazel (Continuum, 2009)
Draws on contemporary conduct books, letters, diaries, journals, and newspapers to create insight into marriage in the late eighteenth and early nineteenth centuries.
Keywords: Austen, Jane / 1775-1817 / Criticism and interpretation; Austen, Jane <1775-1817> -- Criticism and interpretation; Austen, Jane -- 1775-1817; Geschichte 1800-1900; Geschichte 1775-1817; Women and literature / England / History / 19th century; Marriage in literature; Women in literature; Man-woman relationships in literature; Geschichte; Women and literature -- England -- History -- 19th century; Frau; Soziale Rolle; Ehe -- Motiv; Großbritannien